Literasi Digital dan Pencegahan Pelanggaran Undang-Undang Informasi dan Transaksi Elektronik (ITE) di RT. 38 RW. 001 Kelurahan Sungai Andai - Sulastri; Sahrul; Ziyada Wulan Wulida (LPPI UMN AL WASHLIYAH, 2026)
This community service activity aims to increase the legal knowledge and awareness of the residents, specifically those of RT. 38 RW. 001 in Sungai Andai Village, to foster prudent behavior in using digital media in accordance with statutory regulations. Employing methods of presentation, discussion, Q&A, and case studies, the activity was executed as planned and met its objectives. Positive impacts were evident in the enhanced understanding and legal consciousness of the community, particularly among homemakers, regarding digital literacy and the provisions of the Information and Electronic Transactions (ITE) Law. The achievement is reflected in the targeted participant attendance, their active engagement during sessions, and their ability to relate the presented material to legal issues encountered in daily life. This was demonstrated through various feedback and questions from participants concerning problems such as cyberbullying, defamation, the spread of hoaxes and indecent content, and efforts to prevent online gambling within the family. These conditions indicate that this legal outreach activity successfully addressed the community's real needs in tackling legal challenges in the digital era.